Taman Bacaan Dengan Pendekatan Arsitektur Ekologis Di Kota Singaraja, Kabupaten Buleleng - I Made Agus Brastama Andhiriksa; I Gede Surya Darmawan; Ida Bagus Gede Parama Putra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Reading Park with an ecological architectural approach are designed to meet the needs or reading rooms in Singaraja City which are considered to be lacking. The design approach uses the principles of ecological architecture because of the need for harmony between nature and humans themselves. Ecological principles will be implemented in urban areas where the area is prone to environmental damage. As for later several civitas who will use this public facility, namely students, people with disabilities, and the people of Singaraja City. The reading park will also be designed to be friendly to people with disabilities. Several facilities to support the convenience of the disabled will also be available at this reading park. It is hoped that the activities and facilities in this reading park can run in harmony and become a reading room and study room that is able to answer problems in the city of Singaraja.